2011
DOI: 10.1111/j.1551-2916.2011.04985.x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Aspects of Kaolinite Based Coal Mining Wastes in Pozzolan/Ca(OH)2 System

Abstract: The transformation process of the natural kaolinite into metakaolinite for its use as a cement addition was very much known long time ago. However, environmental policies prioritize the waste recycling as raw material by its environmental benefits. This article reports, for the first time, the scientific aspects related to the recycling of three Spanish coal mining wastes of different nature and origin, as an alternative source to obtain future pozzolans based on metakaolinite. The effect of activation conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 28 publications
2
39
0
2
Order By: Relevance
“…Previous study showed the formation of hemicarboaluminate and monocarboaluminate in paste containing 30 wt.% MK and 15 wt.% limestone, while significant amount of limestone remained in the paste (Antoni et al, 2012). Other studies indicated the formation of monocarboaluminate in pastes containing MK and lime (Frias and Cabrera, 2001;Zibara et al, 2008;Aggelakopoulou et al, 2011;Frias et al, 2012;Gameiro et al, 2012;Tironi et al, 2013). In this study, the formation of hemicarboaluminate and monocarboaluminate is thermodynamically feasible through the carbonation of specimen by CO 2 in the atmosphere (Duan et al, 2012).…”
Section: Hydration Productsmentioning
confidence: 62%
“…Previous study showed the formation of hemicarboaluminate and monocarboaluminate in paste containing 30 wt.% MK and 15 wt.% limestone, while significant amount of limestone remained in the paste (Antoni et al, 2012). Other studies indicated the formation of monocarboaluminate in pastes containing MK and lime (Frias and Cabrera, 2001;Zibara et al, 2008;Aggelakopoulou et al, 2011;Frias et al, 2012;Gameiro et al, 2012;Tironi et al, 2013). In this study, the formation of hemicarboaluminate and monocarboaluminate is thermodynamically feasible through the carbonation of specimen by CO 2 in the atmosphere (Duan et al, 2012).…”
Section: Hydration Productsmentioning
confidence: 62%
“…The social and economic impact of metakaolinite production has prompted the publication of many studies on alternative sources of this pozzolan [7][8][9]. Paper manufacture, like any other industry, generates huge volumes of different types of waste, classified in the European List of Waste (ELW).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies are interested in their use in the field of civil engineering. Frias et al [2] [3] are interested on pozzolan properties of coal waste. They study the activation of kaolinite, contained in coal mining waste, to metakaolinite which can be an alternative source to obtain pozzolans .…”
Section: Introductionmentioning
confidence: 99%